Three dimensional left atrial volume index is correlated with P wave dispersion in elderly patients with sinus rhythm - ÖZBEN SADIÇ, BESTE (SPRINGER WIEN, 2016)
Background P wave dispersion is a noninvasive electrocardiographic predictor for atrial fibrillation. The aim of the study was to explore relation between left atrial volume index assessed by 3-dimensional echocardiography and P wave dispersion in elderly patients. Methods Seventy-three consecutive patients over the age of 65 (mean age: 75 +/- 7 years, 17 men) were included. P wave dispersion is calculated as the difference between maximum and minimum P wave durations. Left atrial volume index was measured by both 2-dimensional and 3-dimensional echocardiography and categorized as normal (a parts per thousand currency signaEuro parts per thousand 34 mL/m(2)) or increased (mild, 35-41 mL/m(2); moderate, 42-48 mL/m(2); severe, a parts per thousand yenaEuro parts per thousand 49 mL/m(2)). Results Thirty-one patients had normal left atrium while 24 patients had mildly enlarged, nine had moderately enlarged, and nine had severely enlarged left atrium. Prolongation of P wave dispersion was more prevalent in patients with dilated left atrium. P wave dispersion was significantly correlated with both 2-dimensional (r = 0.600, p < 0.001) and 3-dimensional left atrial volume index (r = 0.688, p < 0.001). Both left atrial volume indexes were associated with prolonged P wave dispersion when adjusted for age, sex, presence of hypertension, and left ventricular mass index. Receiver-operator characteristic (ROC) analysis revealed that a 3-dimensional left atrial volume index a parts per thousand yenaEuro parts per thousand 25 mL/m(2) separated patients with prolonged P wave dispersion with a sensitivity of 82.2 %, specificity of 67.9 %, positive predictive value of 80.4 %, and negative predictive value of 70.4 %. Conclusion In elderly patients, 3-dimensional left atrial volume index showed a better correlation with P wave dispersion and might be helpful in discriminating patients with prolonged P wave dispersion, who might be prone to atrial fibrillation.
Keywords: Echocardiography; Electrocardiography; Left atrium; Left atrial volume index; P wave dispersion; RISK-FACTORS; FIBRILLATION; ECHOCARDIOGRAPHY; VALIDATION; PREDICTION; PARAMETERS; STROKE; COHORT